Critical incidents involving Semiology during practical activities of nursing undergraduates - Ídila Letícia Justiniana de Macedo; Cristina Mara Zamarioli; Emilia Campos de Carvalho
ABSTRACT Objective: To identify critical incidents (situations, behaviors and feelings) during practical activities, involving knowledge and skills related to the discipline of Semiology and Semiotics. Method: Descriptive research using the critical incident technique, with the Snow Ball technique for the selection of participants and an instrument for collection of data. The reports were categorized according to the elements of the critical incident (situations, behaviors and feelings). Results: A total of 62 reports from senior (n = 46), sophomore and junior (n = 16) students were analyzed. The students were predominantly female (90.3%). The majority described a situation of a physical examination, expressed mastery of the skills necessary for the activity and reported positive feelings. Conclusion: The reports showed that the knowledge and skills acquired in the discipline allowed for a development of practical activities with familiarity and positive feelings. The importance that the students attribute to the recognition of the activities by the professor, the patient and family stands out.